The Influence Of Brand, Facilities, And Service Quality On Customer Satisfaction At Primadona Service Station - Lili Anggraini; Ocdy Amelia; Husni Muharram Ritonga (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze brand, facilities, and service quality on customer satisfaction at Primadona Service Station. This study used a quantitative method involving 89 consumers as respondents. Data collection was conducted using a questionnaire. The data obtained were analyzed using statistical formulas, including normality tests, multicollinearity tests, heteroscedasticity tests, and multiple linear regression analysis using SPSS Version 23.0. The results of this study indicate that brand has a positive and significant effect on customer satisfaction with a t-value of 4.380 and a significance of 0.000 <0.05. Facilities have a positive and significant effect on customer satisfaction with a t-value of 2.508 and a significance of 0.014 <0.05. Service quality has a positive and significant effect on customer satisfaction with a t-value of 2.173 and a significance of 0.033 <0.05. Brand, facilities, and service quality simultaneously influence customer satisfaction, with an F-value of 72.698 with a significance level of 0.000 < 0.05.